2008
DOI: 10.1101/gad.1719908
|View full text |Cite
|
Sign up to set email alerts
|

The S. pombe SAGA complex controls the switch from proliferation to sexual differentiation through the opposing roles of its subunits Gcn5 and Spt8

Abstract: The SAGA complex is a conserved multifunctional coactivator known to play broad roles in eukaryotic transcription. To gain new insights into its functions, we performed biochemical and genetic analyses of SAGA in the fission yeast, Schizosaccharomyces pombe. Purification of the S. pombe SAGA complex showed that its subunit composition is identical to that of Saccharomyces cerevisiae. Analysis of S. pombe SAGA mutants revealed that SAGA has two opposing roles regulating sexual differentiation. First, in nutrien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
122
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(139 citation statements)
references
References 74 publications
17
122
0
Order By: Relevance
“…For example, genome-wide characterization of Gcn5-responsive genes reveals that Gcn5 functions as both a coactivator and a corepressor in S. cerevisiae and Schizosaccaromyces pombe (Xue-Franzen et al 2010). Gene expression studies have also shown that Gcn5 and subunits of the SAGA TBP-binding module have opposing roles; S. cerevisiae SPT3 and GCN5 mutations were found to have opposite effects in transcriptional regulation of the HO and STE11 genes (Yu et al 2003;Helmlinger et al 2008), although it is possible that some of these phenotypes are due to indirect effects. SAGA can also repress basal expression of some genes in vitro and in vivo (Belotserkovskaya et al 2000;Warfield et al 2004).…”
Section: Saga Organization and Tbp Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, genome-wide characterization of Gcn5-responsive genes reveals that Gcn5 functions as both a coactivator and a corepressor in S. cerevisiae and Schizosaccaromyces pombe (Xue-Franzen et al 2010). Gene expression studies have also shown that Gcn5 and subunits of the SAGA TBP-binding module have opposing roles; S. cerevisiae SPT3 and GCN5 mutations were found to have opposite effects in transcriptional regulation of the HO and STE11 genes (Yu et al 2003;Helmlinger et al 2008), although it is possible that some of these phenotypes are due to indirect effects. SAGA can also repress basal expression of some genes in vitro and in vivo (Belotserkovskaya et al 2000;Warfield et al 2004).…”
Section: Saga Organization and Tbp Bindingmentioning
confidence: 99%
“…These mutations are presumably altered in their interaction with TBP because several can be suppressed in an allele-specific fashion by mutations in TBP. However, the interaction of SAGA and TBP is complex because mutations in Spt3 and Spt8 can have both positive and negative effects on gene expression (Yu et al 2003;Helmlinger et al 2008). Both Spt3 and Spt8 crosslink to TBP in PICs (Mohibullah and Hahn 2008), and mutations in Spt3 and Spt8 show defects in TBP recruitment in vivo (Dudley et al 1999;Larschan and Winston 2001;Bhaumik and Green 2002;Barbaric et al 2003;Mohibullah and Hahn 2008).…”
Section: Saga Organization and Tbp Bindingmentioning
confidence: 99%
“…In fission yeast, the SAGA complex consists of 19 subunits, all of which are conserved in budding yeast (13). SAGA contains the histone acetyltransferase (HAT) catalytic subunit, Gcn5 (12,14).…”
mentioning
confidence: 99%
“…SAGA contains the histone acetyltransferase (HAT) catalytic subunit, Gcn5 (12,14). Deletion of gcn5 ϩ in fission yeast results in a global decrease in acetylation of histone H3 residues Lys-9, Lys-14, and Lys-18, but changes the expressions of only a relatively small subset of genes (1-2%) by more than 2-fold (13,15). SAGA is known to control sexual differentiation in S. pombe (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation